On-farm evaluation of seed yield and oil quality of linseed (Linum usitatissimum L.) in inland areas of Tuscany, Central Italy - Angelini, Luciana G.; Tavarini, Silvia; Antichi, Daniele; Foschi, Lara; Mazzoncini, Marco (Italian Journal of Agronomy, 2016)
Traditional oilseed crops, such as linseed (Linum usitatissimum L.), may represent valuable alternative crops in cropping systems dominated by cereals, due to their adaptability to poor soils and to their high economic value related to the interesting quality of the oil, which is being increasingly appreciated by consumers and industry. The aim of this study was to test the adaptability of linseed to the inland marginal areas of Tuscany, and to explore the levels of crop yield and oil quality which can be achieved in hilly and lowland environments. For three years (2011-2014), experimental open fields (1- 5 ha each) were established and monitored in six commercial farms located in the inland countryside of Pisa province, Tuscany, Central Italy. The effect of environment (hilly and plain areas) was assessed in terms of yield and yield components as well as oil content and composition. Interestingly, seed yield and biomass production were very stable over years in the two areas of cultivation, irrespectively of yearly differences in weather conditions. As expected, higher yields were obtained in plain than in hilly areas. Regarding oil composition, oil extracted from linseed grown in plain environments was richer in linolenic acid, while, oppositely, both oleic and linoleic acids were more abundant in oil from hilly areas. Definitively, our results demonstrated that linseed might be a valuable alternative to cereal crops for marginal lands of Tuscany and, more in general, of Central Italy.